ASSOCIATIONS BETWEEN POLYMORPHISM OF GROWTH HORMONE GENE WITH MILK PRODUCTION, FAT AND PROTEIN CONTENT IN FRIESIAN HOLSTEIN CATTLE - Hartatik, T.; Kurniawati, D.; Adiarto, A. (Diponegoro University, 2015)
The aim of the research was to determine the associations between polymorphism of the bovine growth hormone (GH) gene (Leu/Val) and milk production of Friesian Holstein Cattle. A total of 62 cows which consist of two Friesian Holstein cattle groups (from New Zealand=19 heads and Australia=43 heads) were used for the research. We performed the Polymerase Chain Reaction and followed by Restriction Fragment Length Polymorphism using AluI restriction enzyme. The genotype was observed base on the target gene GH 211 bp in the part of intron 4 and exon 5 of growth hormone gene. The frequencies of genotypes LL were found higher than genotype LV in both groups. Friesian Holstein cattle from New Zealand showed the genotype LL and LV as 84% and 16%, respectively. Friesian Holstein cattle from Australia show the genotype LL and LV as 79% and 21%, respectively. The association between Leu/Val polymorphism on milk production, fat and protein content in both groups did not show the significant effect. Base on two groups of the origin of cattle, the result showed the significant different on fat and protein content of milk. Fat and protein contents of milk were higher in breed of FH imported from Australia compared to those in breed of FH imported from New Zailand.